Body-mass management of Australian lightweight rowers prior to and during competition - Slater, G. J.; Rice, A. J.; Sharpe, K.; Mujika, I.; Jenkins, D.; Hahn, A. G. (Medicine & Science in Sports & Exercise, 2005)
Purpose: Although the body-mass management strategies of athletes in high-participation weight-category sports such as wrestling have been thoroughly investigated, little is known about such practices among lightweight rowers. This study examined the body-mass management practices of lightweight rowers before competition and compared these with current guidelines of the International Federation of Rowing Association (FISA). Quantification of nutrient intake in the 1-2 h between weigh-in and racing was also sought.